Fuel from waste: electrosynthesizing ammonia directly from agricultural digestate through ligand isomerization - Mendhe, Rahul Mahadeo; Mondal, Ritwik; Kottaichamy, Alagar Raja; Haridas, Akshay; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thimmappa, Ravikumar; Thotiyl, Musthafa Ottakam (Green Chemistry, 2024)
We demonstrate that the catalytic metal centre for ammonia production can be selectively activated with only a slight alteration in ligand isomerization (alpha and beta isomers), making it practical and effective even for agricultural effluents. With almost 90% faradaic efficiency, the beta isomer generates approximately 0.64 mg h-1 cm-2 of ammonia. Energy-efficient ammonia recovery is made possible by the interfacial proton charge assembly that beta-isomerization creates, which attracts the reacting nitrate and repels the competing hydronium ions. With minimal energy consumption, this isomerization approach can interconvert agricultural effluents into ammonia fuel, reaching up to 84% of its theoretical yield and maintaining stability over 100 hours of continuous electrolysis. Ligand isomerization driven ammonia electrosynthesis from agricultural waste water.